Chaotic decayes in resonators filled with rare plasma - Antonov, A.N.; Buts, V.A.; Kovalchuk, I.K.; KovpikKovpik, O.F.; Kornilov, E.A.; Svichensky, V.G.; Tarasov, D.V. (Вопросы атомной науки и техники, 2008)
The results of processes theoretical and experimental investigation of the broadband chaotic HF oscillations in the electrodynamics structure with rare plasma are presented. They are based on the nonlinear decay of HF wave into new HF and LF ones. The natural waves which may take part in this interaction are defined. There is a good agreement between theoretical and experimental results.